Education in West Africa - Amoako, Emefa (Education around the world series, 2015)
Education in West Africa is a comprehensive critical reference guide to education in the region. Written by regional experts, the book explores the education systems of Benin, Burkina Faso, Cameroon, Cape Verde, Chad, The Gambia, Ghana, Guinea, Guinea-Bissau, Ivory Coast, Liberia, Mali, Mauritania, Niger, Nigeria, Senegal, Sierra Leone and Togo. It critically examines the development of education provision in each country, whilst exploring both local and global contexts. Including a comparative introduction to the issues facing education in the region as a whole, this handbook is an essential reference for researchers, scholars, international agencies and policy-makers at all levels.